2012
DOI: 10.1097/icl.0b013e31823bad0e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cellular Debris on Pseudomonas aeruginosa Adherence to Silicone Hydrogel Contact Lenses and Contact Lens Storage Cases

Abstract: These results demonstrate that prolonged corneal inflammation with the presence of PMNs when confronted with simultaneous PA challenge in extended contact lens wear has the potential to stimulate biofilm formation on silicone hydrogel contact lenses. These findings further suggest that a persistent buildup of extracellular debris in lens storage cases may contribute to the heavy biofilms reported on these surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…12, 13 Lens-attached bacteria can readily form biofilms with enhanced resistance to antimicrobials, 14 and P. aeruginosa biofilms formed on contact lenses show greater density and viable bacteria when formed in the presence of phagocytic cells or corneal epithelial debris. 15, 16 These data are consistent with our studies using a contact lens wear in vivo rodent model of Pseudomonas keratitis which showed extensive biofilm formation on posterior lens surfaces associated with the development of microbial keratitis 17 . These infections occurred after several days of continuous lens wear suggesting that bacterial adaptation was needed to the ocular environment in order for infection to occur.…”
Section: Lens Materials and Bacterial Colonization Of The Contact Lenssupporting
confidence: 88%
“…12, 13 Lens-attached bacteria can readily form biofilms with enhanced resistance to antimicrobials, 14 and P. aeruginosa biofilms formed on contact lenses show greater density and viable bacteria when formed in the presence of phagocytic cells or corneal epithelial debris. 15, 16 These data are consistent with our studies using a contact lens wear in vivo rodent model of Pseudomonas keratitis which showed extensive biofilm formation on posterior lens surfaces associated with the development of microbial keratitis 17 . These infections occurred after several days of continuous lens wear suggesting that bacterial adaptation was needed to the ocular environment in order for infection to occur.…”
Section: Lens Materials and Bacterial Colonization Of The Contact Lenssupporting
confidence: 88%
“…Therefore while tears contain a plethora of antimicrobial molecules few/none may be effective against organisms in a biofilm on a contact lens placed on to the eye. In keeping with this S.marcescens biofilms on etafilcon A lenses were resistant to phagocytosis by neutrophils (Hume et al, 2003) and some P. aeruginosa strains show enhanced biofilm formation in the presence of neutrophils (Burnham et al, 2012). …”
Section: Modulation Of Tear Antimicrobialsmentioning
confidence: 55%
“…7,13 Factors that may be ameliorated by single-use daily disposable (DD) lenses Copyright 2015 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 compared to reusable lenses are 5.43 higher risk due to infrequent lens storage case replacement, 19 6.43 higher risk with poor case hygiene, 19 bioburden on the SCL, 18 and bioburden of the SCL storage case. [20][21][22] Compared to use of reusable contact lenses, DD lenses were associated with a 12.53 lower risk of CIEs when worn on a DW basis in a large US case-control study, 13 but in an earlier UK case-control study, one brand was associated with a 2.73 increased risk of sterile keratitis (CIEs). 15 In the United States, DD lenses have an increasing market share, with a trend from approximately 10% in 2006 to approximately 25% of all SCL fits from 2008 forward.…”
mentioning
confidence: 96%